PENGARUH PEMBERDAYAAN MUSYAWARAH GURU MATA PELAJARAN (MGMP) TERHADAP KINERJA GURU DI KABUPATEN CIAMIS - Mohamad Dudi Solahuddin (Journal Of Regional Public Administration (JRPA), 2017)
This study is focused on obtaining a picture of the effect of MGMP empowerment on teacher performance in Kabupaten Ciamis conducted at 32 MGMP. The research approach used quantitative approach with explanatory survey method of correlation technique and regression test. Research data collected through questionnaire. The results show that (1) score of items with total score of empowerment MGMP has positive relationship this indicates that the implementation of MGMP activity in Kabupaten Ciamis has reached ideal; (2) score of item with total score of teacher performance have positive correlation, thus the performance of teacher following MGMP empowerment in Kabupaten Ciamis has reached ideal; (3) The empowerment of MGMP has a strong influence on teacher performance with contribution of 24.21% while the remaining 75.79% is determined by other variables. The result of the analysis shows that the regression line is Y = 59,394 + 0,725X. This shows that if there is no increase of MGMP empowerment variable value, the teacher's performance value is 59,394, and each addition of one MGMP empowerment score will give teacher performance score increase of 0.725. The probability value of 0.000 is smaller than 0.05. It can be concluded that significant regression coefficients, or MGMP empowerment really have a significant effect on teacher performance.